2023
DOI: 10.3390/jof9020240
|View full text |Cite
|
Sign up to set email alerts
|

In Candida glabrata, ERMES Component GEM1 Controls Mitochondrial Morphology, mtROS, and Drug Efflux Pump Expression, Resulting in Azole Susceptibility

Abstract: Mitochondrial dysfunction or morphological abnormalities in human pathogenic fungi are known to contribute to azole resistance; however, the underlying molecular mechanisms are unknown. In this study, we investigated the link between mitochondrial morphology and azole resistance in Candida glabrata, which is the second most common cause of human candidiasis worldwide. The ER-mitochondrial encounter structure (ERMES) complex is thought to play an important role in the mitochondrial dynamics necessary for mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, F 1 complex dysfunction did not contribute to the increased cycloheximide tolerance (Zhang & Moye‐Rowley, 2001). Acquired azole resistance in C. glabrata has been linked to mitochondrial dysfunction, although the underlying molecular mechanism is unclear (Defontaine et al., 1999; Ferrari et al., 2011; Gale et al., 2023; Okamoto et al., 2023; Sanglard et al., 2001). In a separate report, Gale et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, F 1 complex dysfunction did not contribute to the increased cycloheximide tolerance (Zhang & Moye‐Rowley, 2001). Acquired azole resistance in C. glabrata has been linked to mitochondrial dysfunction, although the underlying molecular mechanism is unclear (Defontaine et al., 1999; Ferrari et al., 2011; Gale et al., 2023; Okamoto et al., 2023; Sanglard et al., 2001). In a separate report, Gale et al.…”
Section: Discussionmentioning
confidence: 99%
“…The authors put forth an alternative hypothesis that Pdr1 functions as an indirect sensor of cellular stresses, rather than a direct sensor of xenobiotic stress. A recent study hypothesized that it is the increased mitochondrial ROS levels arising from mitochondrial dysfunction that leads to Pdr1‐dependent upregulation of efflux pumps (Okamoto et al., 2023). It has previously been shown that azoles localize to the mitochondria of C. albicans (Benhamou et al., 2017) and that C. glabrata gains transient fluconazole resistance through reversible loss of mitochondrial function (Kaur et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated mt-ROS is also implicated in acquiring drug resistance, for instance in Candida glabrata -azole resistance. A deficiency in the ERMES (ER-mitochondrial encounter structure) component GEM-1 leads to mt-ROS generation, along with mitochondrial dysfunction and azole efflux pump upregulation, leading to azole resistance [ 177 ]. Fungal mitochondria have a completely different take when inducing pathogenicity.…”
Section: Mitochondrial Ros In Fungal Infectionsmentioning
confidence: 99%
“…In the case of C. glabrata, the primary mechanism driving azole resistance involves the upregulation of efflux pumps, particularly CDR1, which is mediated by a transcription factor, PDR1 [17][18][19][20][21][22][23][24]. Other studies have also highlighted that azole resistance coincides with stress induced by mitochondrial loss or dysfunction, leading to the activation of PDR1, and subsequently, the upregulation of CDR1 [25][26][27][28][29][30]. Furthermore, as a strategy for azole resistance in C. glabrata, our attention has been directed towards the role of host cholesterol uptake.…”
Section: Introductionmentioning
confidence: 99%